2007
DOI: 10.1016/j.ajog.2007.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fecal and urinary incontinence on quality of life 6 months after childbirth

Abstract: Objective-The objective of the study was to investigate the impact of postpartum fecal incontinence (FI) and urinary incontinence (UI) on quality of life (QOL). Study Design-Seven hundred fifty-nine primiparous women in the Childbirth and PelvicSymptoms study were interviewed 6 months postpartum. FI and UI were assessed with validated questionnaires. We measured QOL with SF-12 summary scores, health utility index score (a measure of self-rated overall health), and the modified Manchester Health Questionnaire.R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 25 publications
(39 reference statements)
2
55
1
3
Order By: Relevance
“…The reality is that UI has a serious psychological affect on women, and leads to social seclusion and economic burden (Herzog, Diokno, Brown, Fultz, & Goldstein, 1994;Segedi et al 2011). The QoL of participants who complained of UI post-CSD was negatively affected, which is similar to another study in this area (Handa et al 2007). This, coupled with other postoperative complications as well as a baby, can be extremely stressful for a woman postpartum, especially if she does not understand what is happening to her body.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The reality is that UI has a serious psychological affect on women, and leads to social seclusion and economic burden (Herzog, Diokno, Brown, Fultz, & Goldstein, 1994;Segedi et al 2011). The QoL of participants who complained of UI post-CSD was negatively affected, which is similar to another study in this area (Handa et al 2007). This, coupled with other postoperative complications as well as a baby, can be extremely stressful for a woman postpartum, especially if she does not understand what is happening to her body.…”
Section: Discussionsupporting
confidence: 76%
“…This could be because HIVinfected women who are already socially excluded by social stigma (Gilbert & Walker, 2010) now have to cope with UI, which can be embarrassing. However, UI can be avoided or corrected, because effective treatments are available (Handa et al 2007;Mantle, Haslam & Barton 2004). Health care professionals caring for postpartum patients should therefore screen them in order to identify UI at follow-up visits (Handa et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women with 2° perineal tears had an 80% increased incidence of dyspareunia at 3 months postpartum and women with 3° and 4° tears had a 270% increased incidence of dyspareunia. Pelvic organ prolapse, urinary incontinence, and anal incontinence correlate significantly with sexual dysfunction [25,26] and the importance of pelvic floor exercises during pregnancy and postpartum cannot be stressed enough as a way to decrease urinary and anal incontinence at 12 months [27].…”
Section: Woman's Response To Pregnancymentioning
confidence: 99%
“…Urinary incontinence (UI) is a significant health concern and has been shown to impair women's activities and also affects the physical and mental health [1]. Studies on UI have reported a prevalence of 32%-64% for all UI and 40-59% for stress urinary incontinence (SUI) including mixed incontinence [2].…”
Section: Introductionmentioning
confidence: 99%